Trend dan Peluang Penelitian Environmental Auditing: Kajian Biliometrik 2015-2025 - Ayu Widiastuti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Environmental management auditing is a strategic tool used to assess an organization’s performance in environmental management. Its main objectives are to enhance compliance with regulations, identify environmental risks, and strengthen corporate social responsibility. This study uses a bibliometric approach to analyze trends and research opportunities in the field of environmental management auditing during the period 2015–2025. Utilizing the Publish or Perish and VOSviewer software, this study examines 200 publications obtained through Google Scholar, revealing citation patterns, author collaborations, and frequently occurring keywords in the literature. The analysis results show that topics such as auditing, disclosure, governance, and big data dominate the existing literature, reflecting significant attention to transparency and data management in environmental audits. Additionally, there is a noticeable shift toward the use of technology in environmental auditing practices, including the use of big data and analytics to support audit processes. Bibliometric visualization also identified several areas with low density, such as implementation and environmental information, indicating potential research opportunities. This suggests that although significant research has been conducted, there is still room for further development, particularly regarding the implementation of environmental management audits across various industries. This study provides valuable insights into the development of more adaptive, multidisciplinary environmental auditing strategies that align with sustainable development goals.